Corporate Conception in Terrorism Based on Act No. 5 Of 2018 - Parikhesit Parikhesit; Gunarto Gunarto; Maryanto Maryanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Enforcement strategies terrorism has changed from that previously used the law enforcement strategy reactive (reactive law enforcement) to the law enforcement proactive (proactive law enforcement). Enforcement strategies are proactive expected to reach the corporate as well as those who are behind it as the founders, leaders and corporate board into the hands of the main perpetrators of criminal acts of terrorism.The purpose of writing is to know the conception of the corporation in criminal acts of terrorism and how the system of corporate criminal liability in criminal acts of terrorism under the Act No. 5 of 2018.Act No. 5 of 2018 recognize the corporation as a subject or as a criminal. While the forms of criminal acts committed by a corporation is the criminal acts committed by individuals. Thus the corporation can be said to be committing a crime as stipulated in the formulation of a criminal offense if the offense is committed by people on the basis of employment, or other relation, either individually or jointly, acting for and on behalf of the corporation in and outside the corporate environment.The setting is the principal criminal fines against corporations show that the conception of the corporation in criminal acts of terrorism under the Act No. 5 of 2018 is the third model is the corporation as a maker as well as corporate responsibility.Keywords: Corporate; Accountability; Terrorism.